2019
DOI: 10.1038/s41598-019-54011-6
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency photomodulators for millimeter wave and THz radiation

Abstract: Photomodulators for mm-wave and THz radiation are an essential component for many imaging and signal processing applications. While a myriad of schemes have been devised to enhance photomodulation by enhancing the light-matter interaction, there has been less focus on the photoconductive materials themselves, which are often the limiting factor. Here, we present an approach to increase the photomodulation efficiency of silicon by orders of magnitude, using post treatment of off-the-shelf silicon wafers. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…However, for samples S1 and S9, both of which have almost the same optical reflectivity, as shown by Figure 3, the former has much smaller terahertz MF than the latter. This is because the dielectric layer added on top of the silicon surface terminates dangling bonds that arise due to the lattice termination, resulting in a reduction in trap density [18]. Therefore, we show that the SiO 2 not only plays a role of chemical passivation, but also acts as an anti-reflection film that enhances the use of light energy [26].…”
Section: Thz Photomodulation Experimentsmentioning
confidence: 78%
See 1 more Smart Citation
“…However, for samples S1 and S9, both of which have almost the same optical reflectivity, as shown by Figure 3, the former has much smaller terahertz MF than the latter. This is because the dielectric layer added on top of the silicon surface terminates dangling bonds that arise due to the lattice termination, resulting in a reduction in trap density [18]. Therefore, we show that the SiO 2 not only plays a role of chemical passivation, but also acts as an anti-reflection film that enhances the use of light energy [26].…”
Section: Thz Photomodulation Experimentsmentioning
confidence: 78%
“…While various approaches have been adopted to boost photomodulation [15][16][17], there has been less focus on the semiconducting photoconductive materials themselves. Quite recently, Hooper et al [18] demonstrated that a passivated silicon wafer can greatly improve the efficiency of THz photomodulation. However, THz single-pixel imaging based on such a THz photomodulator has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that another Si modulator that exhibits high MD greater than 80% is previously realized at similar short λ of 623 nm. [ 31 ] In that case by passivating the Si surface the lifetime of the excess carrier in the silicon surface is greatly increased, leading to a large surface photoconductive and notably enhanced modulation efficiency. Both modulators work well under low power density, thus eliminate the need for intense laser sources.…”
Section: Resultsmentioning
confidence: 99%
“…However, these film‐coated Si modulators generally cannot suppress the light reflection or maintain the same high modulation efficiency at a very short illumination light wavelength. One interesting modulator is the surface‐passivated Si modulator, as we mentioned before, [ 31 ] which can provide a very high MD (≈80–100%) at 623 nm by increasing the carrier lifetime from the intrinsic 10 µs to ≈50 ms. However, the long carrier lifetime decreases the modulation speed to tens of Hz while increases the lateral diffusion lengths of the carrier to 7 mm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation